Evaluation Existential of Medical Record Laboratory at the Diploma 3 Program for Medical Record & Health Information, Mathematics and Natural Science Faculty, Gadjah Mada University - Savitri Citra Budi; Hariyono Hariyono; Sri Purwatiningsih (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2006)
The availability of Medical Record Laboratory to support Medical Record education is one that the education provider should prepare. In addition, education providers should also organize the usage, instrument provision, HRD provision and clear planning and objectives.The present research used evaluation topic on the existence of Medical Record Laboratory at the Diploma 3 Program for Medical Record and Health Information, MIPA Faculty, Gadjah Mada University. This topic was used by considering the Government Regulation on education provision, especially Medical Record Education (The Regulation of Minister Health Number 1192/Menkes/Per/X/2004) as thinking base. Data were taken from initial survey that the Laboratory was considered as not maximally performed. Base on instrument availability, this laboratory had no complete instrument, especially manually data processing completeness. Moreover, in fact, the usage and planning on this facility had not been well organized, while there was mostly high demand on the usage. To this end, evaluation was highly required for future progress. Evaluation was gradually performed. First was evaluation on input related technology, human resources, costs, facilities and management. Second was evaluation on process related to whether the planned activities had been completed or not. Third, evaluation on inputs related to attitudes, norms and skill knowledge of those involved in the laboratory (staffs, students, and stakeholder).The present research exploited descriptive method with qualitative approach using single data variable (the existence of Medical Record Laboratory at the Diploma 3 Program for Medical Record and Health Information Gadjah Mada University). Data were collected using source triangulation approach through data cross-checking with fact from other sources. Data analysis was performed by comparing data taken to the existing standard (Government Regulation and theory). To simplify discussion, data were discussed based on principle elements of health services, among others, including: inputs, process, and outputs.Evaluation on the existence of laboratory was presumably exploited to consider future development and management as expected that this Laboratory could be taken as example for medical record management in hospitals.